Newtonian mechanics a modelling approach - Raine, Derek J. 1946- (Dulles, Virginia Mercury Learning and Information, 2017)
Newtonian mechanics is taught as part of every physics program for several reasons. It is a towering intellectual achievement; it has diverse applications; and it provides a context for teaching modelling and problem solving. This text gives equal prominence to all three missions.
Mechanical models -- Forces -- Kinematics -- Energy -- Motion -- Momentum -- Orbital motion -- Oscillations -- Rigid bodies -- Stability of motion -- Lagrangian and Hamiltonian mechanics.
Includes index.
Keywords: Mechanics -- Textbooks; Physics -- Textbooks